The Effect of Metacognitive Scaffolding Strategy in Improving English Writing Skill at Senior High School Students - Issyatul Mardiah; Isnaini Sya’roin; Muh Junaidi (Humanitatis : Journal of Language and Literature, 2023)
The research aims to determine whether metacognitive scaffolding strategy has an effect on improving the English writing skill of making argumentative paragraphs of academic writing and how metacognitive scaffolding strategy can improve the English writing skill of senior high school students at Madrasah Aliyah Mu'allimat Nahdlatul Wathan Anjani. The quantitative research method used was a true experiment with a pretest-posttest control group design. The research sample was 33 students from the school with 17 students in the experimental class using the metacognitive scaffolding strategy and 16 students in the control class using the conventional strategy, and the study lasted four weeks. The mean pre-test for the experimental class was 48.94 and 50.75 for the control class. Using the paired sample t-test, the mean post-test of the experimental class showed a significant improvement; the mean was 74, or 14 points more than the control class. By using this significant value, the researcher tested the effect size using Cohen’s d test. The experimental class's Cohen's d value was 1.59, indicating that this learning strategy is very effective in improving students' writing, according to Cohen's d table for measuring variable effectiveness. Therefore, the metacognitive scaffolding strategy has an effect on improving writing skills in senior high school students. Furthermore, students showed positive results in their leadership, critical thinking, and problem-solving ability.